Clinical efficacy and safety of imepitoin in comparison with phenobarbital for the control of idiopathic epilepsy in dogs. Issue 2 (31st July 2014) - Tipold, A.; Keefe, T. J.; Löscher, W.; Rundfeldt, C.; de Vries, F.
<x xml:space="preserve">Abstract</x> The anticonvulsant activity and safety of imepitoin, a novel antiepileptic drug licensed in the European Union, were evaluated in a multicentre field efficacy study as well as in a safety study under laboratory conditions. Efficacy of imepitoin was compared with phenobarbital in 226 client‐owned dogs in a blinded parallel group design. The administration of imepitoin twice daily in incremental doses of 10, 20 or 30 mg/kg demonstrated comparable efficacy to phenobarbital in controlling seizures in dogs. The frequency of adverse events including somnolence/sedation, polydipsia and increased appetite was significantly higher in the phenobarbital group. In phenobarbital‐treated dogs, significantly increased levels of alkaline phosphatase, gamma‐glutamyl‐transferase and other liver enzymes occurred, while no such effect was observed in the imepitoin group. In a safety study under laboratory conditions, healthy beagle dogs were administered 0, 30, 90 or 150 mg/kg imepitoin twice daily for 26 weeks. A complete safety evaluation including histopathology was included in the study. A no‐observed‐adverse‐event level of 90 mg/kg twice daily was determined. These results indicate that imepitoin is a potent and safe antiepileptic drug for dogs.